The Tradition of Reading Asma'ul Husna in al-Muhsin Mosque, Krapyak, Yogyakarta - Aulan Ni'am (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
In its development a lot of religious traditions that emerged in the community, especially religious traditions carried out in a mosque, a place where the center of worship of Muslims in congregation. Masjid Jami 'Al-Muhsin Krapyak Wetan is one of them, there is a tradition that is constantly being carried out and has become a part of worship at the mosque. The tradition of recitation of Asma'ul Husna at the Jami Mosque 'Al-Muhsin Krapyak Wetan is a unique phenomenon, in which there are interesting things in terms of normative and historical. With qualitative-field research methods and using a phenomenological approach, the tradition will be presented so that it becomes a comprehensive study and provides interesting information. This study gets a conclusion that from the tradition there are several things that make the tradition to be lasting. Namely the existence of a person who becomes a role model, then there is awareness of knowledge about the things that support the implementation of the tradition continuously. All of these things support one another for the continuation of the tradition of reading Asma'ul Husna at the Mosque.